(3GdHQgGf aj Yde GdHjGfs - (3VjGA GdOjf Hf GdGKjQs
(3ChdgG (B:s
(3GdHdGZI EgOGA GdeYfi Zdi GdbdH ai CMSf UhQI ef GddaGX eY GdEjLGR ZjQ GdeNd Ch GdGWfGH ZjQ Gdeed ef ZjQ JYH Ydi GdeNGWH s
(3BNQgG (B:s
(3cJTHjg GdNO HGdhQO hGdbO HGdZUf hGdYjf HYjf GdegGg hGdYfb HYfb GdXHi hEHQjb GdPgH hGdaVI s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3CdeGfjG s
Keywords: (3GdHdGZIs